Colossians-Philemon : a begining-intermediate Greek reader - Jeal, Roy R. (Wilmore, KY : GlossaHouse, 2015)
"A tier 3 resource designed to build confidence in understanding Greek and to encourage the reading of the Greek New Testament by providing: vocabulary glosses, morphological explanations and translation helps."
Includes bibliographical references.
Text in English and Koine|| Greek.
Keywords: Bible. -- Translating; Bible. -- Translating; Bible. -- Translating; Greek language, Biblical -- Translating into English